A Relative Viewpoint of Spiritual Revival and Sociable Rebellion In Gibran K. Gibran and W. Blake: The Influence of William Blake on Kahlil Gibran's Spiritual and Sociopolitical Vision (Journal of Advances and Scholarly Researches in Allied Education, 2014)
There is evidence that Gibran was familiar with some of Blake’s poetryand drawings during his early years in Boston. However, this knowledge of Blakewas neither deep nor complete. Kahlil Gibran was reintroduced to WilliamBlake’s poetry and art in Paris, perhaps in Auguste Rodin’s studio and by Rodinhimself. It was then that Gibran read Blake’s works more completely and studiedhis biography and also viewed many more reproductions of his drawings. InParis, Gibran was called “the twentieth-century Blake,” and from that time on,Blake played a special role in Gibran’s life. Their reading of the Bible, theirrebellion against church corruption, and their sociopolitical visions were verysimilar.  Both Gibran and Blake were poets and artists. Both rebelled against thedecayed and rigid laws of church and society. Both rejected Reason in the nameof Imagination and read the Bible in its “Diabolical form.” Above all, the twopoets shared a basic prophetic vision and apocalyptic view of the universe.Throughout their works, the messianic mission of the poet and the function ofthe artist is clear. Poetry is to lead the people back to Eden, and paintingmust be a step from nature toward the infinite.